U–Pb Geochronology and Stable Isotope Geochemistry of Terrestrial Carbonates, Lower Cretaceous Cedar Mountain Formation, Utah: Implications for Synchronicity of Terrestrial and Marine Carbon Isotope Excursions - Erik L. Gulbranson; E. Troy Rasbury; Greg A. Ludvigson; Andreas Möller; Gregory A. Henkes; Marina B. Suarez; Paul Northrup; Ryan V. Tappero; Julie A. Maxson; Russell S. Shapiro; Kathleen M. Wooton (Geosciences, 2022)
The terrestrial Lower Cretaceous Cedar Mountain Formation, Utah, is a critical archive of paleoclimate, tectonics, and vertebrate ecology and evolution. Early Cretaceous carbon cycle perturbations associated with ocean anoxia have been interpreted from this succession, as expressed in stable carbon isotopes. However, refining the timing of the observed stable isotope excursions remains a key challenge in understanding how marine anoxia affects the Earth system, and is ultimately recorded in the terrestrial realm. The geochronology and geochemistry of a terrestrial carbonate near the base of this succession, which potentially records the Ap7 global carbon isotope excursion, is studied here. Petrographic and geochemical analyses are used to test plausible mechanisms for U incorporation into the calcite lattice in this sample. Using these methods, the hypothesis that the incorporation of U was at or close to the timing of carbonate precipitation is evaluated. U–Pb geochronology of calcite indicates a plausible Early Cretaceous age. However, comparison of the new U–Pb ages of calcite with detrital zircon maximum depositional ages immediately beneath the studied sample indicates a disparity in the apparent sedimentation rates if both types of geochronologic information are interpreted as reflecting the timing of sediment deposition. The totality of data supports an early, and high-temperature, diagenetic timing of U incorporation, with potential for minor leaching of U in subsequent fluid–rock interaction. The most likely mechanism for U transport and immobilization in these samples is hydrothermal fluid–rock interaction. Therefore, the radiometric ages, and corresponding stable isotope composition of U-bearing carbonate domains in this sample, indicate early subsurface fluid–rock interactions and not a record of atmosphere–soil geochemical reactions.